In Vitro, In Vivo, and In Silico Analysis of Pyraclostrobin and Cyprodinil and Their Mixture Reveal New Targets and Signaling Mechanisms - BEREKETOĞLU, CEYHUN (My University, 2024)
Pyraclostrobin and cyprodinil are broad-spectrum fungicides that are used in crops to control diseases. However, they are excessively used and, as a result, end up in the environment and threaten human health and ecosystems. Hence, knowledge of their mechanisms of action is critical to revealing their environmental fate and negative effects and regulating their use. In the present study, we conducted a comprehensive study to show the adverse effects of pyraclostrobin, cyprodinil, and their mixture using zebrafish larvae and different cell lines. Several end points were investigated, including mortality, development, gene expression, reporter assays, and molecular docking simulations. We found that both compounds and their mixture caused developmental delays and mortality in zebrafish, with a higher effect displayed by pyraclostrobin. Both compounds altered the expression of genes involved in several signaling pathways, including oxidative stress and mitochondrial function, lipid and drug metabolisms, the cell cycle, DNA damage, apoptosis, and inflammation. A noteworthy result of this study is that cyprodinil and the mixture group acted as NFκB activators, while pyraclostrobin demonstrated antagonist activity. The AHR activity was also upregulated by cyprodinil and the mixture group; however, pyraclostrobin did not show any effect. For the first time, we also demonstrated that pyraclostrobin had androgen receptor antagonist activity.
Keywords: Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; TOKSİKOLOJİ; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; TOXICOLOGY; Toksikoloji; Toxicology; Animals; Ecosystem; Humans; Molecular Docking Simulation; Pyrimidines; Strobilurins; Zebrafish; cyprodinil; pyrachlostrobin; pyrimidine derivative; strobilurin; animal; ecosystem; human; metabolism; molecular docking; zebra fish